A Review of Student Deposit and Withdrawal Processes at the Bank Sumsel Babel UNSRI Cash Office - Sipa Pitonna Putri; Hendri Gunawan; Diana Widhi Rachmawati (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
This study examines the deposit and withdrawal processes of student funds at the Bank Sumsel Babel Cash Office, Sriwijaya University. Using a qualitative descriptive approach, data were collected through direct observation, interviews with bank staff and students, and documentation of Standard Operating Procedures (SOPs). The findings indicate that transaction procedures have generally been implemented in accordance with banking standards and supported by an integrated core banking system. However, several challenges remain, including errors in transaction slip completion, long queues during peak hours, limited cash availability at certain times, and occasional system disruptions. The study concludes that while the services operate effectively overall, improvements in customer education, service efficiency, and technological infrastructure are needed to enhance service quality for students.